1985
DOI: 10.1111/j.1365-2621.1985.tb01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different types of carrageenans and carboxymethyl celluloses on the stability of frozen stored minced fillets of cod

Abstract: Different types of carrageenans and carboxymethyl celluloses were used as additives (5 g/kg) for minced fillets of cod. Samples of these treatments were stored at -18°C for 10 weeks and were evaluated at regular intervals for pH, water holding capacity, texture, extractable myosin and formation of dimethylamine and formaldehyde.Except Kappa carrageenan the additions improved the water holding capacity of the raw and cooked minced fish and decreased toughening during frozen storage. The addition of Iota carrage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The results shown in Tables 2 and 3 are in good agreement with the ones presented elsewhere for cooked samples with similar additions (da Ponte et al, 1985b;da Ponte et al, 1985~). In those experiments the increase in water holding capacity was attributed to the increase in viscosity brought about by CMC and xanthan additions and to the formation of a gel in the case of iota carrageenan.…”
Section: Weight Loss and Fat Uptakesupporting
confidence: 91%
“…The results shown in Tables 2 and 3 are in good agreement with the ones presented elsewhere for cooked samples with similar additions (da Ponte et al, 1985b;da Ponte et al, 1985~). In those experiments the increase in water holding capacity was attributed to the increase in viscosity brought about by CMC and xanthan additions and to the formation of a gel in the case of iota carrageenan.…”
Section: Weight Loss and Fat Uptakesupporting
confidence: 91%
“…We have found no reference in the literature to addition of fruit fibre to a fish product. DaPonte et al. (1985) and DaPonte et al.…”
Section: Resultsmentioning
confidence: 99%
“…We have found no reference in the literature to addition of fruit fibre to a fish product. DaPonte et al (1985) and DaPonte et al (1987) reported higher water retaining capacity for other kinds of fibres (carrageenan, xanthan, carboxylmethylcellulose) in frozen minced products. Sa´nchez-Alonso et al (2007a) reported a decrease in the water binding capacity of MFM with added wheat fibre when water was added to keep the moisture constant.…”
Section: Water Binding Capacity Of Mince With Added Grape Antioxidantmentioning
confidence: 97%
See 1 more Smart Citation
“…Many of the dietary fibres currently used for technological purposes in fishery products are highly soluble and come from algae such as carrageenans (Borderías, Montero, & Mati de Castro, 1996;DaPonte, Herfst, Roozen, & Pilnik, 1985;Foegeding & Ramsey, 1987; Gó mez-Guillén, Solas, Ortiz & Aguilera, 2004), or from seeds such as garrofin, guar, xanthan and others (Montero, Hurtado, & Pérez-Mateos, 2000;Pérez-Mateos, Hurtado, Montero, & Fernández-Martín, 2001). Although known to possess excellent water binding ability, these ingredients cause extensive loss of rigidity and elasticity in muscle protein gels (Yoon & Lee, 1990;Borderias, Sánchez-Alonso, & Pérez-Mateos, 2005).There is very limited experience in the use of insoluble dietary fibres, such as cereal dietary fibres, in fishery products (Yoon & Lee, 1990;Ang & Miller, 1991).…”
Section: Introductionmentioning
confidence: 99%